Phonological Interference Of Arabic In Learning English As Second/Foreign Language - Vijay Shankar Prasad (Elementary Education Online, 2023)
Mother Tongue Interference is a remarkable aspect of second/foreign language learning. This interference is more in speaking skill than writing skill. This is due to the different sound and their articulating systems in different languages. This is the same with Arabic and English. The number of sounds in Arabic language is about 34 while in English it is 44. In Arabic there is just 6 or 8 vowel sounds and in English 20. So, a learner who becomes habituated to articulate mother tongue sounds has difficulty in mastering second/foreign language sounds. The present Research Paper deals with some of those difficulties in Arabic background learners of English. their phonological reasons and the ways that may be helpful in removing those difficulties. . In this regard we have given much emphasis on listening and speaking practices. We are fortunate that we have radio, TV, Internet and other devices where we can easily find native speakers speaking well or news readers making correct pronunciation. The learners are strictly advised to read newspapers, journals, and other books to facilitate themselves more and more exposure to English that may reduce the interference to a greater extent if not completely.